General Summability Factor Theorems and Applications - Rhoades, B. E.; Savaş, Ekrem (Sarajevo Journal of Mathematics, 2024)
We obtain sufficient and (different) necessary conditions for the series $\sum a_{n}$, which is absolutely summable of order $k$ by a triangular matrix method $A$, to be such that $\sum a_{n}λ_n$ is absolutely summable of order $k$ by a triangular matrix $B$. As corollaries we obtain a number of inclusion theorems. 2000 Mathematics Subject Classification. Primary: 40G99; Secondary: 40G05, 40D15